TOURISM'S MACROECONOMIC CONTRIBUTION AND POST-PANDEMIC RESILIENCE: GDP AND EMPLOYMENT DYNAMICS, 2015-2025, WITH PROJECTIONS TO 2030 - B. Sobirov (PT ANTIS INTERNATIONAL PUBLISHER, 2026)
Objective: The COVID-19 pandemic delivered the sharpest contraction in the modern history of tourism, providing a natural experiment in the sector's macroeconomic weight and resilience. Method: This study analyses the trajectory of tourism's contribution to global gross domestic product and employment over 2015-2025 and projects it to 2030. Results: Tourism's GDP share, stable at about 10.3 percent on the eve of the pandemic, collapsed to 5.5 percent in 2020 - a 47 percent contraction - before recovering to 10.3 percent by 2025; its employment share fell more modestly, from 10.3 to 8.4 percent (a 18 percent contraction), and recovered to 10.9 percent. The asymmetry between the deep, V-shaped output contraction and the shallower, more persistent employment adjustment is the study's central empirical finding, indicating substantial labour retention and a slower but ultimately fuller employment recovery. Trend projection points to continued expansion of both shares through 2030. Novelty: The results quantify tourism's macroeconomic significance, characterize its resilience profile, and inform counter-cyclical and workforce policy.